A Study of Instagram Reels Exploring the Interplay of User Motivations, Attitudes, and Continuance Intentions in Short-Form Video Content - LEE, Jeong Sun; CHA, Seong Soo (Journal of Management World, 2025)
This study investigates the relationships between user motivations, attitudes, and continued usage intentions for Instagram Reels, while examining the moderating role of consumption value orientations. Employing structural equation modeling with data from 352 users, we find that interactivity, entertainment, and escapism significantly influence attitudes, which strongly predict continued usage intentions. Our multi-group analysis reveals that hedonic and utilitarian consumption values moderate these relationships. Entertainment has a significantly stronger effect on attitudes for hedonic users, while interactivity and informativeness show stronger, though non-significant, associations for utilitarian users. Escapism exhibits divergent effects across groups, positive for hedonic users and negative for utilitarian users. Notably, self-expressiveness demonstrates a strong positive association with attitudes across both groups, suggesting its universal appeal. These findings extend Uses and Gratifications Theory to short-form video contexts and highlight the nuanced role of consumption values in shaping user engagement. The study offers valuable insights for platform developers and content creators, suggesting the need for tailored strategies that address the diverse needs of users with different consumption value orientations. As social media continues to evolve, understanding these nuanced relationships becomes increasingly crucial for both researchers and practitioners in the field, enabling more targeted and effective platform design and content strategies across various short-form video platforms. This research contributes to the growing body of literature on social media user behavior and provides practical implications for enhancing user engagement in the rapidly evolving landscape of short-form video content.